TOXIGENIC MOLDS ON FISH FEEDS-I: IMPACT OF CLIMATIC FACTORS - DAS, MEENAXI; PRASAD, SHAMBHU; VERMA, SHISHIR K. (Journal of Indian Fisheries Association, 2015)
The present communication is a survey report carried out to assess theincidence of toxic mycoflora on seven types of agriculture products/byproductsincorporated during fish culture as supplementary dietary items. Sampleswere obtained from various sources at Darbhanga, Madhubani andSamashtipur districts during summer, winter and monsoon months. Out ofthe total 177 4 samples, only 894 appeared to be fresh visually reflectingaverage incidence of contamination around 46.6%. However, the apparentlyfresh samples, when subjected to culture, 26.9% of them were found to becontaminated. Thus, degree of fungal spoilage in feed ingredients in parts ofnorth Bihar appears to be significantly high (73.5%). The present studyillustrates the facts with special reference to Aspergillus flavus, A parasiticus(elaborating aflatoxins) A. ochraceous, Penicilium viradicatum (elaboratingochratoxins) andAversicolor (elaborating sterigmatocystin). The other strainsalready known for their toxigenic potentials that appeared on the presentsubstrates included A. niger, A. fumigatus, A. candidus, P. islandicum,Rhizopus spp. and Mucur spp. Studies indicate that the prevelent climaticfactors like temperature and relative humidity facilitate a congenial conditionalmost all through the year and in particular during summer and monsoonmonths. But water content of the substrates is a vital factor that furtheraccelerates the pace of mycobial spoilage. A thorough sun-drying of theagricultural commodities before prolonged storage to bring water contentbelow the ''low risk limit" may significantly reduce the incidence of molds.Keywords : Toxigenic molds, fish feeds, fungal spoilage